Enhancing madrasah’s excellence through innovative leadership: A case study at Madrasah Tsanawiyah Negeri 1 Bireun - Amalia, Ilmi; Rahmi, Jumailatul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This study explores the role of innovative leadership in advancing the excellence of Madrasah Tsanawiyah Negeri (MTsN) 1 Bireuen. Employing a qualitative descriptive approach, data were collected through interviews, observations, and document analysis involving the school principal and subject teachers. The findings indicate that the principal exhibits a comprehensive understanding of innovative leadership by promoting teacher autonomy, adopting novel instructional models, facilitating professional development, and encouraging community engagement. Notable innovations identified include student character development, the integration of digital learning technologies, and enhancements to school infrastructure. The study concludes that innovative leadership is pivotal in cultivating a collaborative, adaptive, and high-quality learning environment within Islamic educational settings.